Compact Dual-Mode Bandpass Filters Based on Half-Mode Substrate-Integrated Waveguide Cavities - Zhu, Fang; Luo, Guo Qing; Liao, Zhen; Dai, Xi Wang; Wu, Ke (IEEE microwave and wireless components letters, 2021)
This letter presents a novel class of compact dual-mode bandpass filters based on half-mode substrate-integrated waveguide (HMSIW) cavities. By using both TE 102 and TE 301 modes of the HMSIW rectangular cavity as resonant modes and TE 101 mode as nonresonating mode, a novel HMSIW doublet with two poles and two transmission zeros (TZs) is implemented. The TZs can be located at one side or both sides of the passband. Therefore, flexible responses can be obtained. A two-pole HMSIW filter with asymmetric response and a four-pole HMSIW filter with quasi-elliptic response have been designed, fabricated, and measured, to demonstrate and verify the proposed structure. Compared with substrate-integrated waveguide (SIW) counterparts, the dual-mode HMSIW filters have the advantage of smaller size.